2021
DOI: 10.1002/jpen.2216
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral probiotics administration on the expression of transforming growth factor β and the proinflammatory cytokines interleukin 6, interleukin 17, and tumor necrosis factor α in skin wounds in rats

Abstract: Background: Cytokines and growth factors play key roles during the tissue repair process. We aim to evaluate the effect of perioperative oral of probiotics, on the healing process in skin wound in rats, by histological aspects, and by the expression of TGF-β, and the pro-inflammatory cytokines IL6, IL7, and TNF-α.Methods: 72 adult male Wistar rats were split into two groups control (n = 36) and probiotic group (n = 36). Each group was subdivided into three subgroups with 12 animals each according to euthanasia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…Therefore, L-SF/ SA may have important prospects in improving wound healing and reducing fibrotic scar. Similarly, Tagliari et al 42 reported that oral probiotics were associated with a shorter inflammatory phase by attenuating the expression of cytokines IL-6 and TNF-α and accelerating the reduction of TGF-β, leading to faster and improved cutaneous healing in rats. Kanmani et al 43 showed that LAB strains (Lactiplantibacillus plantarum, Lactobacillus brevis, and Weissella cibaria) attenuated hepatic stellate cell (HSC) activation mediated by the profibrotic cytokine TGF-β, thereby preventing liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, L-SF/ SA may have important prospects in improving wound healing and reducing fibrotic scar. Similarly, Tagliari et al 42 reported that oral probiotics were associated with a shorter inflammatory phase by attenuating the expression of cytokines IL-6 and TNF-α and accelerating the reduction of TGF-β, leading to faster and improved cutaneous healing in rats. Kanmani et al 43 showed that LAB strains (Lactiplantibacillus plantarum, Lactobacillus brevis, and Weissella cibaria) attenuated hepatic stellate cell (HSC) activation mediated by the profibrotic cytokine TGF-β, thereby preventing liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Deneklerde 10. günde tip I kollajen ve 7. günde ise tip III kollajen üretimi artmıştır. PB uygulaması için inflamatuar fazı azaltarak, fibrozis sürecini gerileterek ve kollajen birikimini artırarak yara alanının daha olgun tedavisi sağlanmıştır [26,27]. Bu bulgular ile bizim sonuçlarımız uyumlu ve paraleldir.…”
Section: Discussionunclassified
“…The most predominant species of probiotics studied as new therapeutical strategies for their capacity to promote wound healing, making them ideal healing candidates, include lactic acid bacteria (LAB) such as Lactobacillus plantarum , L. acidophillus , L. fermentum L. paracasei , L. rhamnosus , L. bulgaricus , L. reuteri , L. delbreuckii , L. salivarus, and Bifidobacterium lactis [ 25 , 29 ]. LAB are Gram-positive, microaerophilic, and non-sporulating microorganisms with health benefits for the host, especially regarding dermal health, by improving the regulation of the skin and mucosa immune system and by maintaining cutaneous homeostasis [ 30 ].…”
Section: Types Of Probiotics In Wound Healingmentioning
confidence: 99%